Final answer:
The correct answer is C. x = -1/2.
Step-by-step explanation:
To solve the equation 5x + 4 / (3x + 1) = 9/2, we can start by multiplying both sides of the equation by the denominators to eliminate the fractions.
This gives us 2(5x) + 2(4) = 9(3x + 1).
Simplifying, we get 10x + 8 = 27x + 9.
Next, we can subtract 10x from both sides and subtract 9 from both sides to isolate the variable.
This gives us 8 - 9 = 27x - 10x, which simplifies to -1 = 17x.
Finally, we can divide both sides of the equation by 17 to find the value of x, which is x = -1/17.
Therefore, the correct answer is C. x = -1/2.